The effect of Kinesio taping on static and dynamic balance, vertical jump, pain and functional performance in athletes with the anterior cruciate ligament injury - Karimijashni, M.; Ghanbari, A.; Rezaei, S.; Abbasnia, K. (International Journal of Applied Exercise Physiology, 2020)
Background: Anterior cruciate ligament (ACL) has a high incidence in athletes and non-athlete population. One of the main problems in individuals with ACL-injury is defective proprioception and balance control ability. Taping is widely used as a tool for both treatment and prevention of ACL-injuries. Purpose: The purpose of this study was to evaluate the effect of knee kinesio taping on static and dynamic postural control, vertical jump and pain response in athletes with ACL injury. Methods: Forty Four athletes with ACL-injury aged 18 to 45 participated in this study. Subjects were randomly divided into two groups: 1) kinesio tape, 2) placebo. Vertical jump, Single leg stance (SLS) and Star Excursion Balance Test (SEBT) were taken from all subjects. All tests were performed at 3 different conditions: (1) baseline taping; (2) immediately after taping; (3) 24 hours after taping. Data analyzed by SPSS software and repeated-measure variance analysis tests. Results: In this study, we found that the use of kinesio taping in athletes with ACL injury improves static and dynamic balance, vertical jump and also decreases pain in the intervention group. However these variables was not statistically different from the placebo group (P>0.05). Conclusion: The results of this study showed the effectiveness of therapy with kinesio taping. However, further studies are needed to clarify the role of it in ACL injury.